Migrant women and work - Agrawal, Anuja, 1968- (New Delhi ; Thousand Oaks, Calif. ; London : Sage, 2006)
Papers presented at the International Conference on Women and Migration in Asia, held at New Delhi in December 2003.
Introduction : women, work and migration in Asia / Anuja Agrawal -- Asian women workers in international labour migration / Leela Gulati -- Gendering medical migration : Asian women doctors in the UK / Parvati Raghuram -- Caring for the Filipino family : how gender differentiates the economic causes of labour migration / Rhacel Salazar Parreñas -- Towards an analysis of social mobility of transnational migrant women : the case of Filipina domestic workers / Chiho Ogaya -- Beyond duty and desire : reconsidering motivations for Thai women's migration to Bangkok / Alyson Brody -- Indian nurses in the Gulf from job opportunity to life strategy / Marie Percot -- Family, migration and prostitution : the case of Bedia community of North India / Anuja Agrawal -- The traffic in women : human rights violation or migration for work? / Sheila Jeffreys.
Includes bibliographical references and index.
Keywords: Women migrant labor -- Asia; Foreign workers, Asian; Women -- Employment -- Foreign countries